Play behaviour in nonhuman animals and the animal welfare issue - Sarti Oliveira, Ana Flora [UNESP]; Rossi, Andre Oliveira [UNESP]; Romualdo Silva, Luana Finocchiaro [UNESP]; Lau, Michele Correa [UNESP]; Barreto, Rodrigo Egydio [UNESP] (Springer Tokyo, 2010)
The mission of defining animal welfare indicators is methodologically difficult, limited, and possibly impossible. A promising alternative, however, to evaluate suitable environmental conditions is the assessment of play behaviour. In the present review, we summarise the general aspects of play behaviour in nonhuman animals and propose its use as a potential indicator of animal welfare. Play behaviour probably occurs in most vertebrates and some invertebrates, but predominately in mammals. It is also more frequent in young males and is associated with the environmental context in which animals find themselves. Animals play if they are healthy and well-fed, but not if they are under stressful conditions or if they are in a stressful state. We can therefore use the prevalence of play behaviour as an indicator of suitable environmental conditions, considering the specificity associated with the above-mentioned modifying factors.
Keywords: Play behaviour; Animal well-being